2010
DOI: 10.1016/j.intimp.2010.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic potential of placental extract in contact hypersensitivity

Abstract: Immunoregulatory effects of placental extract and placenta-derived factors have been demonstrated in various conditions. Accordingly, placental extract has been used as certain types of medical intervention in Asian countries, whereas experimental evidence supporting its therapeutic effects and mechanisms has yet to be fully demonstrated. In this study, we investigate preventive and therapeutic effects of placental extract in contact hypersensitivity (CHS), a mouse model of allergic contact dermatitis. Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Finally, administration of cyclo-trans-4-L-hydroxy-prolyl-L-serine (JBP485), a dipeptide derived from PE, also alleviated CHS, suggesting its potential role in the effects of PE in CHS. Taken together, these findings demonstrated experimental evidence supporting immunoregulatory effects of PE in allergic skin diseases and elucidated its potential mechanisms [35] .…”
Section: Animal Study Of Placental Extractsupporting
confidence: 61%
“…Finally, administration of cyclo-trans-4-L-hydroxy-prolyl-L-serine (JBP485), a dipeptide derived from PE, also alleviated CHS, suggesting its potential role in the effects of PE in CHS. Taken together, these findings demonstrated experimental evidence supporting immunoregulatory effects of PE in allergic skin diseases and elucidated its potential mechanisms [35] .…”
Section: Animal Study Of Placental Extractsupporting
confidence: 61%
“…Previous studies have demonstrated the immune inhibitory effect of HPE in allergic dermatitis and arthritis . We hypothesize that HPE might impair the distribution of CD4+ T lymphocytes, thereby inhibiting the allergic response.…”
Section: Introductionmentioning
confidence: 85%
“…Hence this can partly explain the reason as to why we did not detect significant change in IL-6 level in our study. Report by Kim et al, showed that placenta extract prevents the development of CHS by decreasing IFN-␥ while increasing IL-4 and IL-10 levels (Kim et al, 2010). They performed subcutaneous implantation of placenta extract 3 days before sensitization which resulted in a significant inhibition of CHS response.…”
Section: Discussionmentioning
confidence: 99%
“…1). Recent work by Kim et al, also showed that treatment of placenta extract significantly decreased CD4 + T cells in the PBMC (Kim et al, 2010). However the role of CD4 + T helper (Th) cells versus CD8 + cytotoxic T (Tc) cells in CHS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation